2017
DOI: 10.4274/meandros.03522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dentofacial and Periodontal Effects of Rapid and Semi-rapid Maxillary Expansion

Abstract: Anah tar Ke li me ler Öz AbstractObjective: The purpose of this study was to compare the skeletal, dentoalveolar and periodontal effects that occurred after rapid maxillary expansion (RME) and semirapid maxillary expansion (SRME) with an acrylic splint bonded expansion appliance and also to compare the degree of root resorption in the supporting teeth during expansion. Materials and Methods:The sample of the study included 19 patients having maxillary constriction requiring bilateral upper premolar extraction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Yildirim and Akin observed the teeth on tissue-borne RME side and more resorption on the buccal surface than on the lingual surface (16). In another study, Gönüldaş evaluated SRME and RME procedures with bonded acrylic splint appliances and researched the buccal root surface changes of supporting teeth with SEM (22). Her study found no statistically significant difference in the amount of resorption between the two groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Yildirim and Akin observed the teeth on tissue-borne RME side and more resorption on the buccal surface than on the lingual surface (16). In another study, Gönüldaş evaluated SRME and RME procedures with bonded acrylic splint appliances and researched the buccal root surface changes of supporting teeth with SEM (22). Her study found no statistically significant difference in the amount of resorption between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has compared skeletal and dentoalveolar changes arising from SME and RME conducted with a tooth support and/or tooth tissue appliances (21,22). However, no research has investigated differences in root resorption in three dimensions among RME, SRME, and SME protocols, which are the most commonly used protocols for upper maxillary expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous orthodontic studies comparing RME and SRME investigated dentoskeletal effects, long-term stability, periodontal effects, nasal airway, and conductive hearing loss. 1,6,[17][18][19] However, no previous study has compared the root resorption occurring after RME and SRME with different appliance designs using micro-CT.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by previous studies in which more root resorption was detected on the buccal surface after RME. 8,10,11,17 Yildirim and Akin 11 compared the bone-borne and tooth-borne RME appliance effects on root resorption using micro-CT. Their study was a well-designed investigation, and the results of the tooth-borne appliance group were very similar to the current study. However, the methodologies were very different between the studies.…”
Section: Discussionmentioning
confidence: 99%